Correlation of cephalometric and anthropometric measures with obstructive sleep apnea severity - Paulo de Tarso M Borges; Edson Santos Ferreira Filho; Telma Maria Evangelista de Araujo; Jose Machado Moita Neto; Nubia Evangelista de Sa Borges; Baltasar Melo Neto; Viriato Campelo; Jorge Rizzato Paschoal; Li M Li (International Archives of Otorhinolaryngology, 2013)
Summary